Desain dan Implementasi Pembersih Panel Surya Otomatis dengan Teknologi IoT pada Penerangan Jalan Umum untuk Kinerja Optimal - Raja Naban, Faisal; Rahmatullah, Daeng (J-Eltrik, 2023)
This paper explores the development and implementation of an automated solar panel cleaning system using IoT technology, aiming to improve the efficiency of solar-powered street lighting (PJU) systems. The accumulation of dirt on solar panels significantly reduces their efficiency, impacting the overall performance of the street lighting system. The proposed system addresses this issue by integrating voltage and current sensors that monitor the panels, with the data processed by a microcontroller using Arduino. This information is then transmitted to the user's smartphone, enabling real-time monitoring and anomaly detection, which facilitates immediate cleaning action when required. The experimental results demonstrate the system's effectiveness, showing an increase in voltage, current, and power output after cleaning. Specifically, the voltage increased from 16.45 V to 17.35 V, the current from 0.52 A to 0.61 A, and the power from 8.55 W to 10.68 W, indicating improved solar energy absorption and conversion. The study highlights the importance of regular maintenance to maintain optimal performance and extend the life of solar panels, offering a cost-effective and reliable solution for public energy infrastructure. The integration of IoT technology overcomes the inefficiencies of manual cleaning methods, which are labour-intensive and costly, while also posing risks of damage and accidents. The IoT-based system enables real-time monitoring and control, improving the reliability and consistency of the cleaning process. This research significantly contributes to the development of effective and efficient solar panel cleaning technologies, promoting sustainable energy solutions for public infrastructure.